Microwave-assisted Synthesis of Functionalized Multiwalled Carbon Nanotube–Titanium Dioxide Hybrid Structure and Photodegradation - Yuyun Irmawati; Shofia Manzalini; Bambang Sugeng; Sudirman Sudirman; Harayasu Asahara; Rike Yudianti (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
Decoration of a functionalized multiwalled carbon nanotube (f-MWCNT) surface with titanium dioxide (TiO2) was designed to improve its photocatalytic degradation performance. Structural decoration was achieved by microwave heating at various mass ratios (1:2; 1:4; 1:8; 1:16 wt.%) of titanium (IV) isopropoxide as precursor. The hybrid structure of TiO2/f-MWCNT was characterized by scanning electron microscope and transmission electron microscope (TEM). The crystallite form of the TiO2 nanoparticles was further studied by X-ray diffraction (XRD) and HR–TEM. We report the conformation of high-density TiO2 coated on an f-MWCNT surface at a mass ratio of 1:16 wt.%. XRD analysis revealed a structural transformation from mixture phase (anatase–brookite) at mass ratios of 1:2 and 1:4 wt.% to fully anatase phase for mass ratios of 1:8 and 1:16 wt.%. The transformation was also confirmed by selected area electron diffraction (SAED) and HR–TEM analysis. Our results showed that anatase phase plays a significant role in photodegradation activity.